2015
DOI: 10.1088/0022-3727/48/35/355202
|View full text |Cite
|
Sign up to set email alerts
|

Streamer knotwilg branching: sudden transition in morphology of positive streamers in high-purity nitrogen

Abstract: We describe a peculiar branching phenomenon in positive repetitive streamer discharges in high purity nitrogen. We name it knotwilg branching after the Dutch word for a pollard willow tree. In a knotwilg branching a thick streamer suddenly splits into many thin streamers. Under some conditions this happens for all streamers in a discharge at about the same distance from the high-voltage electrode tip. At this distance, the thick streamers suddenly bend sharply and appear to propagate over a virtual surface sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…With 0.2% oxygen, small-scale structure and thin branches are visible in the electron density, see figure 10. Such branches have been observed in several experiments in nitrogen and other pure gases, see for example [15,19,20,53]. In these studies, they were referred to as feathers.…”
Section: Morphology At Low Oxygen Concentrationsmentioning
confidence: 86%
“…With 0.2% oxygen, small-scale structure and thin branches are visible in the electron density, see figure 10. Such branches have been observed in several experiments in nitrogen and other pure gases, see for example [15,19,20,53]. In these studies, they were referred to as feathers.…”
Section: Morphology At Low Oxygen Concentrationsmentioning
confidence: 86%
“…To estimate the remaining factors in Equation 3, we first refer to Briels et al (2008), who observed a ratio of branching length to streamer radius of about 20, so a radius of 2 mm at atmospheric pressure translates into ℓ ≈ 6 × 4 cm = 24 cm (Ebert et al, 2010). Finally, we take the branching number b to be 2, although there are evidences that it may possibly be slightly larger (Heijmans et al, 2013(Heijmans et al, , 2015.…”
Section: Streamer Branching Eventsmentioning
confidence: 99%
“…These phenomena are shown in figure 4 where the streamer length versus time is given. As previously used in experiments and simulations [36][37][38], here the streamer length is defined asL 2 , where (x max , y max , z max ) are the maximum electric field coordinate.…”
Section: Dependence On Plasma Density In the Patchmentioning
confidence: 99%